Easter in Ostend : Contemporary Art Confrontation. - Brutin, Hugo (Oostende : Kulturele Kamer, 1992)
Hoeckx, Luc ; De Brabandere, Mario ; Bernier, Pascal ; Riera I Aragó ; De Meester, Karel ; Van Schuylenbergh, André ; Gaube, Bernard ; Ricourt, Wim ; Seynaeve, Johan ; Desguin, Mireille ; De Bruycker, Dirk ; Roelstraete, Stefaan ; Toenges, Michael ; van Grinsven, Servi
Easter in Ostend : Contemporary Art Confrontation, Casino Kursaal, Oostende, 18 - 21 april 1992
Nederlands
kunstcatalogus